Signet ring cell carcinoma of the colon in a 10 year-old boy - Irene Irene; Ketut Ariawati (Indonesian Pediatric Society, 2011)
Signet ring cell carcinoma (SRCC), a variant of adenocarcinoma, is defined by the presence of more than 50% of tumor cells with prominent intracytoplasmic mucin.1 Primary gastrointestinal malignancies constitute only 1% of pediatric neoplasms and 0.34% take the form of colon carcinoma. It is a very rare disease in persons under 17 years of age, 94% of which is found in children> 9 years of age. [.4 In contrast to adults, approximately50% of colon carcinoma cases in children are the highly malignant mucin'producing adenocarcinoma type.4 The typical signet-ring cell has a large mucin vacuole that fills the cytoplasm and pushes the nuclei to the side, thereby giving the cells their signature histologic appearance.S,6 Carcinoma of the colon during childhood has been associated with familialpolyposis and ulcerative colitis. However, carcinoma arising de novo is the most common type.2,3 Risk factors include a high caloric diet rich in animal fat, sedentary lifestyle, smoking, alcohol consumption, low vegetable fibre consumption, chronic inflammatory bowel disease, ulcerative colitis, Crohn's disease, and polymorphism in key enzymes of injurious compounds.s